Сomposition and antioxidant properties of Deschampsia antarctica É. Desv. extracts from different locations of the Maritime Antarctic - Laguta, I.V.; Stavinskaya, O.N.; Kuzema, P.O.; Anishchenko, V.M.; Ivannikov, R.V.; Parnikoza, I.Y.; Poronnik, О.О.; Myryuta, G.Y.; Kunakh, V.A. (Reports of the National Academy of Sciences of Ukraine, 2022)
The composition and antioxidant properties of extracts from Deschampsia antarctica É. Desv. plants collected at different northern islands of Maritime Antarctica were studied. The composition of the extracts was studied using high performance liquid chromatography and mass spectrometry with matrix-assisted laser desorption/ ionization; antioxidant properties were studied using Folin-Ciocalteu method and DPPH test. Polyphenolic compounds, in particular flavonoids, hydroxycinnamic and hydroxybenzoic acids, were found to be the main classes of substances present in the extracts. It has been confirmed that flavonoids are predominantly represented by luteolin glycosides; the composition and amount of phenolic compounds being dependent on the plant genotype, place of origin and environmental conditions. The total polyphenol content in the studied extracts was found to be in the range of 4. 33-10. 93 mg per 1 g of raw material. The highest concentration of active substances was typical for the extracts from plants of the Ukraine Island (the largest of Berthelot Islands), and the lowest one — from plants of the Darboux Island. The results of antioxidant studies have shown that the extracts have high antiradical activity and are able to inhibit more than 50 % of DPPH radicals in 60 min. The data on the composition of polyphenols in Deschampsia antarctica plants can further serve as a marker for monitoring the climate change.